Going green for self or for others? Gender and identity salience effects on sustainable consumption. (25th July 2014) - Costa Pinto, Diego; Herter, Márcia M.; Rossi, Patricia; Borges, Adilson
Abstract The aim of this study is to explore the effects of gender and salient identity on sustainable consumption. In particular, this research investigates how gender effects on sustainable consumption may be contingent to the identity that is salient to the consumer during the evaluation process (personal vs. social). According to identity‐based motivation theory, the salience of personal identity means that people temporarily think about themselves as individuals, whereas social identity salience means that people see themselves as part of a group. The results from an experimental study indicated that when personal identity was salient, female participants declared higher levels of sustainable consumption compared with male participants. However, when social identity was salient, male participants increased their sustainable consumption intentions to the same level as female participants. Finally, this research discusses the theoretical and managerial implications on identities, gender and sustainable consumption.